1978
DOI: 10.1073/pnas.75.8.4057
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of aldosterone secretion by the renin-angiotensin system during sodium restriction in rats.

Abstract: The role of angiotensin II as mediator of the aldosterone response to short periods of sodium restriction was studied in rats by administration of a converting enzyme inhibitor to block formation of the octapeptide throughout the duration of decreased sodium intake. In control animals, short-term sodium restriction caused increased levels of adrenal receptors for angiotensin II, with enhancement of early and late steps in aldosterone biosynthesis and elevation of plasma aldosterone concentration. Each of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1
2

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 37 publications
3
36
1
2
Order By: Relevance
“…The observation that angiotensin converting enzyme inhibitors suppress the increase in plasma aldosterone following sodium deprivation supports the hypothesis that the renin-angiotensin system plays a primary role in the aldosterone response to sodium deprivation. 23,24 However, it is important to note that in this study we observed a reduction in basal aldosterone levels in NaCl-deprived rats treated with DEX. This reduction was not significant in study A, but this was most likely due to the relatively small number of animals and/or the single DEX injection protocol used in that study.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…The observation that angiotensin converting enzyme inhibitors suppress the increase in plasma aldosterone following sodium deprivation supports the hypothesis that the renin-angiotensin system plays a primary role in the aldosterone response to sodium deprivation. 23,24 However, it is important to note that in this study we observed a reduction in basal aldosterone levels in NaCl-deprived rats treated with DEX. This reduction was not significant in study A, but this was most likely due to the relatively small number of animals and/or the single DEX injection protocol used in that study.…”
Section: Discussioncontrasting
confidence: 45%
“…22 Their comparatively modest Ang II-induced aldosterone response was most likely due to the relative unresponsiveness of the adrenals in their rats that were fed a standard laboratory chow containing relatively high levels of NaCl. 22,23 Further illustrating the advantage of the dietary regimen and Ang II infusion rate we have determined to be optimal in this study, other investigators have reported even more modest 2-to 6-fold Ang II-induced increases in plasma aldosterone using various other dietary regimens, drug treatments, and Ang II infusion rates. 2,6,7,18 Although some of these investigators did attempt to inhibit Ang II-induced aldosterone secretion with DEX treatment, none of these investigators provided measurements of plasma ACTH in their studies.…”
Section: Discussionmentioning
confidence: 94%
“…After drastically increasing aldosterone output via mild sodium depletion, ADM did not lower aldosterone secretion in this situation suggesting that, despite having significant inhibitory effects on acutely stimulated ASR, ADM had no role in reducing chronically stimulated aldosterone. Several studies have presented evidence that the steroidogenic response of the zona glomerulosa to sodium depletion is mediated, at least in part, by AngII (Spielman & Davis 1974, Aguilera & Catt 1978. Also, sodium depletion, like AngII, affects aldosterone biosynthesis by altering enzyme activity at a site in both the early (Davis et al 1966) and late (Marusic & Mulrow 1967) biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone, produced by the adrenal glands is stimulated by AII, potassium, and ACTH (Aguilera and Catt 1978). Aldosterone acts in the loop of Henle and distal tubule to promote sodium reabsorption, and in the distal tubule to enhance potassium secretion.…”
Section: Curve Fittingmentioning
confidence: 99%